Electron microscopical study of myocardial biopsy material in congenital heart block. Issue 6 (June 1975) - Ludatscher, R; Amikam, S; Roguin, N; Gellei, B; Riss, E
Abstract : Myocardial tissue from the left ventricle of two children with congenital atrioventricular block and recurrent Admas-Stokes attacks was obtained during the procedure of epicardial pacemaker implantation and studied with the electron microscope. One patient had a familial cardiomyopathy, the other had no clinical abnormality apart from the conduction defect. Proliferation of mitochondria was common in both cases. Focal interstitial fibrosis and pronounced proliferation of transverse tubules were found in the myocardial cells of the patient with familial cardiomyopathy. Deep invaginations of the sarcolemmma with formation of intracytoplasmic channels were present in the second case. The possibility that the numerous transverse tubules could serve as additional pathways for impulse conduction is discussed.